Analisis Proses Pembelajaran Berbasis Online masa Pandemi Covid-19 di SDIT Luqman Al-Hakim Sleman - Wildan Nuril Ahmad Fauzi (eL-HIKMAH: Jurnal Kajian dan Penelitian Pendidikan Islam, 2020)
The research aims to analyze the online learning process during the Covid-19 pandemic in SDIT Luqman Al-Hakim Sleman. This research uses qualitative research with the type of case study. Research to analyze the online learning process during pandemic Covid-19 in SDIT Luqman Al-Hakim Sleman. Data and data sources in this study have basic data and supporting data. The technique for data retrieval in this study is using interviews, then observation, and documentation. Data analysis techniques conducted with data reduction, data presentation, and withdrawal of conclusions (verification). The results of the research of SDIT Luqman Al-Hakim in assisting teachers to prepare online-based learning, by providing subsidies in the form of Internet quota to each teacher, the school gives this help to see online learning requires Internet data, besides the school also provides the account of the school institution. Various distance learning media used is 1) WhatsApp, 2) Zoom Meeting, 3) Google Form, 4) Youtube